2013
DOI: 10.1007/s00429-013-0680-x
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive anatomy of Heschl’s gyri in 430 healthy volunteers, including 198 left-handers

Abstract: This study describes the gyrification patterns and surface areas of Heschl’s gyrus (HG) in 430 healthy volunteers mapped with magnetic resonance imaging. Among the 232 right-handers, we found a large occurrence of duplication (64 %), especially on the right (49 vs. 37 % on the left). Partial duplication was twice more frequent on the left than complete duplication. On the opposite, in the right hemisphere, complete duplication was 10 % more frequent than partial duplication. The most frequent inter-hemispheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 70 publications
(127 reference statements)
8
83
0
Order By: Relevance
“…A similar observation (i.e., of a greater frequency of H2 gyri) has been reported before in individuals with dyslexia, although not specifically in the right hemisphere [Leonard et al, ]. A few studies have shown that the morphology of Heschl's gyri is highly variable in the general population [Leonard et al, ; Marie et al, ; Penhune et al, ]. Additionally, it has been suggested that duplications in the left hemisphere might be related to better skills in phonetic learning and in the auditory processing of speech [Golestani et al, ].…”
Section: Discussionsupporting
confidence: 71%
“…A similar observation (i.e., of a greater frequency of H2 gyri) has been reported before in individuals with dyslexia, although not specifically in the right hemisphere [Leonard et al, ]. A few studies have shown that the morphology of Heschl's gyri is highly variable in the general population [Leonard et al, ; Marie et al, ; Penhune et al, ]. Additionally, it has been suggested that duplications in the left hemisphere might be related to better skills in phonetic learning and in the auditory processing of speech [Golestani et al, ].…”
Section: Discussionsupporting
confidence: 71%
“…Heschl’s gyrus may be a case in point here. This region demonstrated high variability across all 3 cortical metrics in the current study, and other research has documented strong individual variability within this region using various anatomical methods (e.g., Warrier et al, 2009; Marie et al, 2015). Heschl’s gyrus anatomical asymmetry is related to functional asymmetry of auditory processing (Tzourio-Mazoyer et al, 2015; Warrier et al, 2009), and anatomical variation of this region is associated with experiential differences in bilingual language exposure (Ressel et al, 2012), and musical training (Hyde et al, 2009).…”
Section: Discussionsupporting
confidence: 63%
“…In this approach, anatomical labels are assigned by combining local geometric information and atlas data acquired from a manually segmented training set (Desikan et al, 2006;Destrieux, Fischl, Dale, & Halgren, 2010;Fischl et al, 2004). The anterior transverse temporal gyrus (of Heschl) parcellation ("G_temp_sup-G_T_transv") as described in Destrieux et al (2010) (48) Note: Participants were instructed to respond quickly, within a response time limit of 3 s. high interindividual variability and frequent duplications of the transverse temporal gyrus (Leonard et al, 1998;Marie et al, 2015). It thus separates the most anterior gyrus which exclusively contains A1 (Shapleske et al, 1999).…”
Section: Region Of Interest Definitionmentioning
confidence: 99%